Quantitative Analysis of Ingenol in Euphorbia species via Validated Isotope Dilution Ultra-high Performance Liquid Chromatography Tandem Mass Spectrometry - Béres, Tibor; Dragull, Klaus; Pospíšil, Jiří; Tarkowská, Danuše; Dančák, Martin; Bíba, Ondřej; Tarkowski, Petr; Doležal, Karel; Strnad, Miroslav (Phytochemical analysis, 2018)
INTRODUCTION: Various species of the Euphorbia genus contain diterpene ingenol and ingenol mebutate (ingenol-3-angelate), a substance found in the sap of the plant Euphorbia peplus and an inducer of cell death. A gel formulation of the drug has been approved by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for the topical treatment of actinic keratosis. OBJECTIVE: To develop a rapid and reliable method for quantification of ingenol in various plant extracts. METHODOLOGY: Methanolic extracts of 38 species of the Euphorbia genus were analysed via ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS) after methanolysis and solid-phase extraction (SPE) purification. The 18 O-labelled ingenol analogue was prepared and used as an internal standard for ingenol content determination and method validation. RESULTS: The highest ingenol concentration (547 mg/kg of dry weight) was found in the lower leafless stems of E. myrsinites. The screening confirms a substantial amount of ingenol in species studied previously and furthermore, reveals some new promising candidates. CONCLUSION: The newly established UHPLC-MS/MS method shows to be an appropriate tool for screening of the Euphorbia genus for ingenol content and allows selection of species suitable for raw material production and/or in vitro culture initiation. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Euphorbia; rostlinné extrakty; Diterpenes; Plant Extracts; ultra-high performance liquid chromatography; vysokoúčinná kapalinová chromatografie; radioisotopová diluční technika; Chromatography, High Pressure Liquid; mass spectrometry; ingenol; tandemová hmotnostní spektrometrie; diterpeny; Radioisotope Dilution Technique; isotope-dilution method; Tandem Mass Spectrometry; Euphorbia genus